2002
DOI: 10.1079/pns2002194
|View full text |Cite
|
Sign up to set email alerts
|

Does body mass play a role in the regulation of food intake?

Abstract: It is widely believed that body fatness (and hence total body mass) is regulated by a lipostatic feedback system. This system is suggested to involve at least one peripheral signalling compound, which signals to the brain the current size of body fat stores. In the brain the level of the signal is compared with a desirable target level, and food intake and energy expenditure are then regulated to effect changes in the size of body fat stores. There is considerable support for this theory at several different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 109 publications
4
43
1
4
Order By: Relevance
“…Recently, several models have been proposed to explain the set-point theory and its underlying physiological mechanisms. 28,29 According to the proposed models, differences between subjects in body mass might reflect different steady-state set-points of body mass and body fatness, which may interact with a variety of genetic and environmental factors. Under conditions of energy imbalance, whatever the mechanisms and central control systems involved, there is evidence that changes in both appetite and food intake do occur to restore body mass to its centrally encoded set-point.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several models have been proposed to explain the set-point theory and its underlying physiological mechanisms. 28,29 According to the proposed models, differences between subjects in body mass might reflect different steady-state set-points of body mass and body fatness, which may interact with a variety of genetic and environmental factors. Under conditions of energy imbalance, whatever the mechanisms and central control systems involved, there is evidence that changes in both appetite and food intake do occur to restore body mass to its centrally encoded set-point.…”
Section: Discussionmentioning
confidence: 99%
“…This hormone plays the role of a signal that informs the central nervous system of the body's fat status (Meier and Gressner, 2004). The body fat mass is the particular factor that determines plasma leptin concentration in humans (Speakman et al, 2002). In horses, peripheral concentration of plasma leptin is also related to fat mass and body condition score (Buff et al, 2002;Kearns et al, 2006;Gordon et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, physiological research has identified a number of internal post-ingestive processes that trigger the inhibition of appetite. These processes may rely on cues including saliva secretion, gastric acid secretion, insulin release, and several neuropeptides (Schwartz, Woods, Porte, Seeley, & Baskin, 2000;Speakman, Stubbs, & Mercer, 2002). Thus, the question emerges how external visual cues and internal physiological ones interact to influence consumption and satiety.…”
mentioning
confidence: 99%